2022
DOI: 10.1039/d2ra04091c
|View full text |Cite
|
Sign up to set email alerts
|

Co-immobilized bienzyme of horseradish peroxidase and glucose oxidase on dopamine-modified cellulose–chitosan composite beads as a high-efficiency biocatalyst for degradation of acridine

Abstract: Co-immobilized bienzyme biocatalysts are attracting increasing interest in the field of wastewater treatment due to their widespread application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 44 publications
2
4
0
Order By: Relevance
“…Additionally, after 30 days of storage, the activity of free HRP and Mb dropped to 30% of their initial activity, while the activity of immobilized HRP and Mb was greater than 65% after 30 days. These results indicated that immobilization provided a relatively stable microenvironment for HRP and Mb molecules, making them less prone to inactivation during storage [31,49]. This finding is consistent with prior research indicating that calcium alginate does not react with the by-product and can effectively prolong the enzyme's durability, hence resulting in enhanced removal efficiency [50].…”
Section: Stability Of Immobilized Enzymesupporting
confidence: 88%
See 1 more Smart Citation
“…Additionally, after 30 days of storage, the activity of free HRP and Mb dropped to 30% of their initial activity, while the activity of immobilized HRP and Mb was greater than 65% after 30 days. These results indicated that immobilization provided a relatively stable microenvironment for HRP and Mb molecules, making them less prone to inactivation during storage [31,49]. This finding is consistent with prior research indicating that calcium alginate does not react with the by-product and can effectively prolong the enzyme's durability, hence resulting in enhanced removal efficiency [50].…”
Section: Stability Of Immobilized Enzymesupporting
confidence: 88%
“…Water 2024, 16, x FOR PEER REVIEW 8 of 13 immobilization provided a relatively stable microenvironment for HRP and Mb molecules, making them less prone to inactivation during storage [31,49]. This finding is consistent with prior research indicating that calcium alginate does not react with the by-product and can effectively prolong the enzyme's durability, hence resulting in enhanced removal efficiency [50].…”
Section: Single Factor Explorationsupporting
confidence: 83%
“…The combination of GOx and HRP has been widely used either to develop glucose biosensors or to elaborate biofuel cells [ 17 , 18 ]. In this work, the enzyme cascade model involved the sequential reactions of two enzymes as well as a mediated electrical connection step of one enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…First, 0.1 g ZnFe 2 O 4 nanoparticles and 1.0 g PEG-400 were dispersed in 50 mL Tris-HCl buffer (50 mmol•L −1 , pH 8.5), stirred well, and sonicated for 30 min. After the ultrasound, 0.1 g of dopamine (DA) was slowly added to the suspension and mechanically stirred at 300 r•min −1 for 3 h. By selfpolymerizing dopamine in alkaline conditions, nanoparticles coated with polydopamine (PDA) were formed [22]. After the reaction, the separated ZnFe 2 O 4 @PDA nanoparticles were washed with deionized water.…”
Section: Synthesis Of Znfe 2 O 4 @Pdamentioning
confidence: 99%